PENANAMAN NILAI-NILAI BUDI PEKERTI PADA ANAK MELALUI KESENIAN TRADISIONAL - Yuliantoro, Septian (Candi)
The Indonesian nation has progressed in various fields, such as politics, economy, social, culture, and science and technology. Advances in science and technology was also brought harm to young people. To prevent the emergence of adverse effects, it is necessary to character recognition and early learning for children. One way of effective learning manners is through traditional arts. In this article I will describe the values ??embodied in the character of traditional arts, such as leather puppet arts, karawitan, and dance.